EFFECTS OF WAVES ON LEVELS OF STABLE DISSOLVED OXYGEN CONCENTRATION IN COASTAL AREAS - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2019)
Coast organisms need dissolved oxygen (DO) to live. Waters also accommodate plenty of living organisms. Accordingly, oxygen dissolution in water becomes essential in coastal life. The coast is separated into dry, wet and saturated areas in horizontal lines and from the water surface to underneath the sediment in vertical lines. Changes in the DO concentration were investigated at those lines. Experiments were performed in a wave channel that was 24-m long, 1-m wide and 1-m high. In the channel, the coast model had an average sediment diameter of 0.3 mm, a slope of 1/5 and a water depth of 60 cm. The static probe consistently measured the first and the last values as the same for certain levels in each experiment. This refers to no effect of waves on the concentration levels. After the static probe measurements, the DO concentrations were measured on seven vertical lines by moving vehicle at the coast model. Four of the vertical lines were out to sea, two were inland and one was at the shoreline. The DO concentrations in the water were measured above the sea bed and in the sediments on each vertical line. In each experiment, the probe was moved on a vertical line from the bottom towards the water surface for a wave height of H = 11 cm and a wave period of T = 1 s. Measurements made with a static probe and a moving probe were compared, and similar concentrations were found at a given level. All these trials indicated the significant relationship of wave breaks and oxygen dissolutions. We found three vertical lines sufficient in number for additional experiments to observe the different wave parameters. The DO concentration was stable at the following depths below the sea bed (the distance in brackets is that out to sea from the shoreline; the negative value is an inland distance): 10 cm (1 m), 10 cm (0.75 m), 15 cm (0.5 m), 20 cm (0.25 m), 15 cm (0 m) and 20 cm (-0.25 m). Measurements made 0.25 m inland from the shoreline showed that the wave effect did not reach that far. By analysing different wave parameters, the measured wave breaks with constant T and increased H signified their displacement away from shoreline through the open sea. Furthermore, the sand bar's offshore migration occurred with both increased T and H.
Keywords: Dissolved oxygen; Coastal ecosystem; Wave